Manajemen Peserta Didik dalam Meningkatkan Daya Saing di Madrasah - Aisyah Dana Luwihta; Ayu Wahyuning Four Fianti (AKSI: Jurnal Manajemen Pendidikan Islam, 2023)
In realizing quality students who are able to compete in various fields. This study aims to describe the management of students at MA Nurut Taqwa and to describe the competitiveness of students at MA Nurut Taqwa. The approach used in this research is a qualitative approach with a descriptive research type. The method used in data collection is observation related to the implementation of student management in increasing competitiveness, interviews with school principals and student assistants, as well as documentation data and activity archives from management at MA Nurut Taqwa. Researchers use the Miles and Huberman model, namely reduction, presentation and conclusion drawing or data verification. The results of this study indicate that the implementation of student management at MA Nurut Taqwa has been well organized in increasing scientific power which includes: management of new student admissions, activity programs, coaching, evaluation and student achievement.